An Activatable and Switchable Nanoaggregate Probe for Detecting H2S and Its Application in Mice Brains. Issue 21 (6th October 2020) - Qi, Ya‐Lin; Chen, Li‐Li; Guo, Long; Shao, Chen‐Wen; Liu, Ya‐Ni; Yang, Yu‐Shun; He, Zhen‐Xiang; Zhu, Hai‐Liang
Abstract: Employing a sequentially activated probe design method, an activatable, switchable and dual‐mode probe was designed. This nanoprobe, HSDPP, could be effectively activated by H2 S to form H‐type aggregates with green emission; subsequently, the aggregates could bind to mtDNA to form monomers and the emIssion color switched from green to deep‐red. We exploited HSDPP to image exogenous and endogenous H2 S in living cells. Of note, for the first time, this novel nanoprobe with an optimal partition coefficient value (LogP=1.269) was successfully applied for tracking the endogenous H2 S upregulation stimulated by cystathionase activator S ‐adenosyl‐ L ‐methionine (SAM) in mice brains. Finally, our work provides an invaluable chemical tool for probing endogenous H2 S upregulation in vitro/vivo and, importantly, affords a prospective design strategy for developing switchable chemosensors to unveil the relationship between biomolecules and DNA in mitochondria in many promising areas. Abstract : An activatable and switchable nanoaggregate probe for detecting H2 S in mice brains was developed. It could be effectively activated by H2 S to form H‐type aggregates with green emission; subsequently, the aggregates could bind to mtDNA to form monomers and the emission color switched from green to deep‐red.